Vascular Imaging Based Subtyping of Ischemic Stroke in BSMMU - Md Shahidullah, -; Kanti Dey, Subash; Ahmed, Anis; Das, Panchanan; Sultana, Nahid (Bangladesh Journal of Neuroscience, 2019)
Background: Most strokes and stroke related death & disability happened in low and middle income countries. The clinician should be familiar with the sub typing of ischemic stroke patients and the risk factors analysis. Vascular imaging is necessary for classifying the patient. The main objective of this study was to evaluate the subtype of ischemic stroke patients and risk factor analysis of different etiology. Method: This is a hospital based prospective study in Bangladesh. Within the time frame of 2014 March to 2017 November; we analyzed 1978 patients of ischemic stroke within 10 days of symptom onset. Among them 877 patients have been selected for this study to whom brain imaging (CT/ MRI), vascular imaging (MRA, DSA), ECG and echocardiography have been done. We did subtyping according to TOAST criteria. Results: The mean age of patients was 60.5±11 years with 70.47% subjects male and 29.53% female. Within the classification of TOAST, we have found 43.87% of patients were in large artery atherosclerosis group, 23.83.% in small vessel occlusion group, 8.46% in cardiac embolism group, 19.30% in undetermined etiology group and 4.54% in other determined etiology. Among risk factors hypertension in 58.15%, DM was found in 38.42%, hypercholesterolemia in 38.88% of patients. Hypertension was significantly high in large artery atherosclerosis group. Conclusion: In ischemic stroke patients, large artery atherosclerosis was the most common subtype and hypertension was significant in this group. Bangladesh Journal of Neuroscience 2019; Vol. 35 (1): 27-32